2017
DOI: 10.1007/s00122-017-2973-6
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes 1BS and 1RS for control of male fertility in wheats and triticales with cytoplasms of Aegilops kotschyi, Ae. mutica and Ae. uniaristata

Abstract: Engineered chromosomes 1BS and 1RS offer a new alternative in the development of hybrid systems in bread wheat and triticale. In the cytoplasmic male sterility system for hybrid wheat based on the cytoplasm of Triticum timopheevi fertility restoration is difficult, with few good restorer genes available. In the system based on the cytoplasms of Aegilops kotschyi, Ae. uniaristata and Ae. mutica, essentially all chromosomes 1B carry locus Rf that restores male fertility; male sterility manifests itself in wheats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…mutica Bois. 58 can be efficiently restored by the wheat locus Rf multi ( Restoration-of-fertility in multiple CMS systems ) on chromosome 1BS. Replacement of the Rf multi locus by its rye ortholog produces the male-sterile phenotype 59,60 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…mutica Bois. 58 can be efficiently restored by the wheat locus Rf multi ( Restoration-of-fertility in multiple CMS systems ) on chromosome 1BS. Replacement of the Rf multi locus by its rye ortholog produces the male-sterile phenotype 59,60 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the absence of a TraesCS1B02G071642.1 ortholog in the non-restorer rye suggests it as an attractive Rf multi candidate. The only current implementations of a wheat- rye Rf multi CMS system involve 1RS.1BL translocations 5,58,61 , which are typically linked to reduced baking quality 40 . Breaking this linkage may now benefit from marker development and/or genome editing approaches targeting TraesCS1B02G071642.1 .…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the cytoplasm of T. timopheevi , there are several other cytoplasms that also create male sterility in wheat and triticale, mainly from Aegilops species. Lukaszewski () has reported that alloplasmic lines of triticale cv. ‘Presto’ with cytoplasms of Aegilops kotschyi , Aegilops uniaristata , and Aegilops mutica carrying 1D (1B) chromosome substitution are male sterile and that unlike the timopheevi cytoplasm (Curtis & Lukaszewski, ), rye chromosomes of cv.…”
Section: Perspectives Of the Chromosome Manipulations For Triticale Bmentioning
confidence: 99%
“…In wheat, several studies demonstrated positive and negative effects on disease resistance [3,4], photosynthesis and respiration [5], plant height and heading date [6], yield potential [7], seed quality [8], alterations in transcriptomes and metabolomes [9] as well as abiotic stress tolerance [10,11]. However, practical utilization of cytoplasmic diversity and NC interaction in agriculture remains largely unexplored except for well-studied cytoplasmic male sterility and nuclear restoration of fertility for hybrid wheat production [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%